2021
DOI: 10.1177/15589447211052750
|View full text |Cite
|
Sign up to set email alerts
|

Patient Adherence With At-Home Hand and Wrist Exercises: A Randomized Controlled Trial of Video Versus Handout Format

Abstract: Background: Patient adherence is important for maximizing patient outcomes. The purpose of this randomized controlled trial was to determine patient adherence and confidence in home therapy exercises of the hand and wrist at multiple time points when distributed by either paper handout or video. Methods: Patients were prospectively enrolled and randomized in orthopedic clinics to either the handout or video exercise group. Exclusion criteria included patients less than 18 years old. Questionnaires were electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Nonetheless, we provided both groups with an informative brochure containing text and simple illustrations on the general principles of physiotherapy for the treatment of plantar fasciitis, such as rolling or Achilles tendon stretching. Previous studies have suggested that distributing home therapy exercises in a video-format is superior to paper handouts for at-home hand and wrist rehabilitation [38]. It was noted that patients in the video group utilized more exercises and had higher confidence in completing them correctly after starting the exercise program.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, we provided both groups with an informative brochure containing text and simple illustrations on the general principles of physiotherapy for the treatment of plantar fasciitis, such as rolling or Achilles tendon stretching. Previous studies have suggested that distributing home therapy exercises in a video-format is superior to paper handouts for at-home hand and wrist rehabilitation [38]. It was noted that patients in the video group utilized more exercises and had higher confidence in completing them correctly after starting the exercise program.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies were published comparing written and video-based patient educational materials. Patients reported higher satisfaction, better comprehension, safer opioid use, and increased utilization of exercises with video materials compared with written handouts [63][64][65][66] .…”
Section: Practice Management Patient Communicationmentioning
confidence: 99%
“…Specific types of exercises such as grip‐strengthening exercises are often recommended for the improvement of DUL‐MSDs 22 . However, exercise rehabilitation requires completion over several weeks and there are difficulties in sustaining adherence to exercise programmes, 23 with a lack of evidence about intensity and dosage of exercise programmes 22 . Exercise may be optimised with guided self‐management support 24 …”
Section: Introductionmentioning
confidence: 99%